Autologous fibrin scaffolds: When platelet- and plasma-derived biomolecules meet fibrin. (February 2019) - Anitua, Eduardo; Nurden, Paquita; Prado, Roberto; Nurden, Alan T.; Padilla, Sabino
Abstract: The healing of vascularized mammalian tissue injuries initiate with hemostasis and clotting as part of biological defense system leading to the formation of a fibrin clot in which activated platelets are trapped to quickly stop bleeding and destroy microbials. In order to harness the therapeutic potential of biomolecules secreted by platelets and stemmed from plasma, blood deconstruction has allowed to yield autologous platelet-and plasma-derived protein fibrin scaffold. The autologous growth factors and microparticles stemmed from platelets and plasma, interact with fibrin, extracellular matrix, and tissue cells in a combinatorial, synergistic, and multidirectional way on mechanisms governing tissue repair. This interplay will induce a wide range of cell specifications during inflammation and repair process including but not limited to fibrogenesis, angiogenesis, and immunomodulation. As biology-as-a-drug approach, autologous platelet-and plasma-derived protein fibrin scaffold is emerging as a safe and efficacious natural human-engineered growth factor delivery system to repair musculoskeletal tissues, and skin and corneal ulcers and burns. In doing so, it acts as therapeutic agent not perfect but close to biological precision. However, this autologous, biocompatible, biodegradable, and long in vivo lasting strategy faces several challenges, including its non-conventional single dose-response effect, the lack of standardization in its preparation and application, and the patient's biological features. In this review, we give an account of the main events of tissue repair. Then, we describe the procedure to prepare autologous platelet-and plasma-derived protein fibrin scaffolds, and the rationale behind these biomaterials, and finally, we highlight the significance of strategic accuracy in their application.